Near-infrared two-zone three-dimensional covalent organic framework nanomaterial and preparation method thereof
Patent Information
- Application Number
- CN202610796435.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-06-04
AI Technical Summary
(1)缺乏通过不可逆Suzuki偶联构建高结晶性、高稳定性3D COFs的有效策略;
本发明提供的BRT-COF在保持高结晶性的同时,还把具有NIR-II性能的单体引入到BRT-COF的主链中。得益于BRT-COF广泛的π共轭结构及其优异的近红外二区响应特性,该材料表现出良好的组织穿透能力、高空间分辨率、低背景自发荧光干扰以及优异的光热/光动力协同治疗性能,兼具NIR-II成像与肿瘤治疗潜力。
Smart Images

Figure CN122344311B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a near-infrared two-region three-dimensional covalent organic framework nanomaterial and its preparation method, belonging to the technical field of polymer compounds obtained by reactions other than carbon-carbon unsaturated bonds. Background Technology
[0002] Covalent organic frameworks (COFs) are a class of crystalline porous polymer materials composed of lightweight elements (C, H, O, N, S, etc.) linked by covalent bonds. With their high specific surface area, precisely tunable pore structure, excellent structural designability, and good chemical stability, COFs show broad application prospects in gas adsorption and separation, catalysis, photoelectric conversion, and biomedical materials. Among them, three-dimensional covalent organic frameworks (3D COFs) are considered an ideal platform for constructing high-performance functional materials due to their open channels throughout the material volume, even higher specific surface area, and framework stability independent of interlayer stacking. However, the framework construction of existing 3D COFs mainly relies on reversible dynamic covalent chemistry (DCC) reactions such as borate ester condensation and imine condensation. The resulting reversible covalent bonds, such as B–O and C=N, are prone to hydrolysis or dissociation in strong acid, strong alkali, or high humidity environments, leading to framework collapse and performance degradation, severely limiting their application in complex physiological environments and long-term service scenarios.
[0003] In the field of biomedical materials, the near-infrared II (NIR-II, 1000–1700 nm) optical window offers significant opportunities for achieving high-resolution imaging and efficient photoresponse in deep tissues due to its significantly reduced tissue absorption and light scattering characteristics. Developing multifunctional materials that combine NIR-II optical response with photothermal conversion / reactive oxygen species generation capabilities is a cutting-edge research direction in biomedical polymer materials. However, efficiently introducing strong NIR-II absorption / emission groups into the 3D COF framework still faces significant challenges: on the one hand, NIR-II chromophores with D–A–D (donor–acceptor–donor) conjugated structures typically possess high planar rigidity and hydrophobicity, and their direct embedding into the 3D framework easily leads to uncontrollable π–π stacking and interlayer aggregation, thereby causing fluorescence quenching and pore blockage; on the other hand, the topological structure of 3D COFs requires nodes and connecting units to have strictly matched spatial configurations and reactivity, while existing DCC reaction monomer libraries cannot simultaneously meet the NIR-II performance requirements and topological compatibility.
[0004] More importantly, while the Suzuki cross-coupling reaction, as a classic method for constructing carbon-carbon bonds, is widely used in polymer synthesis and the preparation of porous aromatic frameworks (PAFs), its application in the field of COFs has long been limited by technical bias. Those skilled in the art generally believe that Suzuki coupling is an irreversible reaction, lacking the inherent "self-repair" and "error-correction" capabilities of DCC reactions, and therefore cannot yield highly crystalline COFs with long-range ordered pores, only amorphous or low-crystallinity porous polymers. This technical bias has led to very little exploration of the application of Suzuki coupling in constructing highly crystalline 3D COFs in existing research, let alone introducing NIR-II functional groups into 3D frameworks via this route.
[0005] Furthermore, pure COF materials generally exhibit strong hydrophobicity, easily leading to hydrophobic aggregation and precipitation in aqueous and physiological environments. This results in extremely poor dispersibility and insufficient colloidal stability, severely limiting their application as biomedical materials. Existing technologies typically improve their water dispersibility by post-loading dyes or physically coating polymers, but these strategies suffer from problems such as loading leakage, large batch-to-batch variations, and uneven surface modification. Therefore, how to endow COF frameworks with intrinsic NIR-II optical properties through chemical design during the synthesis stage, and achieve stable dispersion in physiological environments through surface engineering, while maintaining the high crystallinity and chemical stability of the 3D framework, has become a key scientific problem and technological bottleneck that urgently needs to be solved in the field of biomedical polymer materials.
[0006] In summary, the existing technology has the following clear drawbacks: (1) There is a lack of effective strategies for constructing highly crystalline and stable 3D COFs through irreversible Suzuki coupling; (2) Existing 3D COFs are difficult to integrate intrinsic NIR-II region fluorescence emission and photothermal / photodynamic properties of the framework; (3) The water dispersibility and colloidal stability of pure COF materials in physiological environments are seriously insufficient, which restricts their biomedical transformation.
[0007] Therefore, there is an urgent need to develop a new type of NIR-II responsive material based on 3D COFs with all-carbon carbon bonds to solve the multiple technical challenges in the material design. Summary of the Invention
[0008] This invention provides a near-infrared two-region three-dimensional covalent organic framework nanomaterial and its preparation method, which can effectively solve the above-mentioned problems.
[0009] This invention provides a method for preparing near-infrared II region three-dimensional covalent organic framework nanomaterials, comprising the following steps: Step (1): The reaction substrate 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) (BRT) and tetra(4-pinacolylphenyl)methane (TPPM) were placed in a reaction vessel and subjected to a Suzuki cross-coupling reaction under alkaline conditions and catalysis by a palladium catalyst. The reaction solvent was a mixture of toluene and ultrapure water, the reaction temperature was 80-120 °C, and the reaction was carried out under inert gas protection for 48-96 h. The molar ratio of the reaction substrate 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) to tetra(4-pinacolylphenyl)methane was 1-5:1. Step (2): After the reaction is completed, let it stand to separate into layers, remove the aqueous phase, add anhydrous ethanol to the organic phase and mix well, centrifuge, discard the supernatant, wash the obtained precipitate alternately with anhydrous ethanol and ultrapure water, and freeze dry to obtain a green solid powder, which is the near-infrared two-region three-dimensional covalent organic framework nanomaterial (BRT-COF).
[0010] In some embodiments, in step (1), the molar ratio of the reaction substrate 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) to tetra(4-pinazolylphenyl)methane is 1.5-3.5:1.
[0011] In some embodiments, in step (1), the palladium catalyst is selected from one or more of tetra(triphenylphosphine)palladium, bis(dibenzylideneacetone)palladium, palladium acetate, and [1,1'-bis(diphenylphosphine)ferrocene]palladium dichloride; the alkaline conditions are provided by at least one of potassium carbonate, sodium carbonate, and cesium carbonate. In some embodiments, the reaction in step (1) is carried out under magnetic stirring at a speed of 100-400 r / min.
[0012] In some embodiments, in step (2), the centrifugation speed is 10000-12000 r / min and the centrifugation time is 5-15 min; the alternating washing is to first wash with anhydrous ethanol 3 times and then wash with ultrapure water 2 times.
[0013] In some embodiments, the above preparation method further includes step (3), which involves surface modification of the BRT-COF obtained in step (2) using ferritin homing peptide.
[0014] In some embodiments, the ferritin homing peptide is HKN. 15 Iron death homing peptide.
[0015] In some embodiments, the surface modification process involves mixing BRT-COF dispersion with HKN. 15 Equal volumes of peptide solutions were mixed thoroughly and sonicated at 3-5 °C, followed by continuous oscillation. After completion, the solutions were purified by centrifugation using an ultrafiltration tube to remove free peptides, and the supernatant was collected.
[0016] This invention provides a three-dimensional covalent organic framework nanomaterial in the near-infrared II region prepared by the above-described method. This nanomaterial exhibits fluorescence emission in the near-infrared II region and simultaneously generates photothermal effects and reactive oxygen species under 808 nm laser irradiation. This invention provides the use of the above-mentioned near-infrared II three-dimensional covalent organic framework nanomaterials in the preparation of near-infrared II fluorescence imaging-guided synergistic photothermal and photodynamic therapy drugs for tumor treatment.
[0017] This invention provides the use of the above-mentioned near-infrared II three-dimensional covalent organic framework nanomaterial in the preparation of near-infrared II imaging reagents. The beneficial effects of this invention are: The BRT-COF provided by this invention maintains high crystallinity while incorporating monomers with NIR-II properties into its main chain. Benefiting from the extensive π-conjugated structure and excellent near-infrared II response characteristics of BRT-COF, this material exhibits good tissue penetration, high spatial resolution, low background autofluorescence interference, and excellent photothermal / photodynamic synergistic therapeutic performance, combining the potential of NIR-II imaging with tumor treatment.
[0018] This invention utilizes the hydrophilic peptide HKN 15 The modified BRT-COF@HKN 15 Composite materials not only retain the excellent optical properties of NIR-II, but also significantly improve their dispersibility, stability and biocompatibility in physiological environments, laying the foundation for efficient in vivo applications.
[0019] Based on existing technical teachings, those skilled in the art would likely prefer to construct COFs using imine condensation reactions and load them with NIR-II dyes. However, the all-carbon-carbon backbone BRT-COF of this invention exhibits significantly better structural stability in physiological environments than imine-bonded COFs (imine bonds are easily hydrolyzed in the tumor microenvironment at pH 5.5-6.5), and its intrinsic NIR-II emission avoids fluorescence signal attenuation caused by dye leakage. Even more unexpectedly, HKN... 15 The modification not only solved the dispersion problem, but also improved the tumor inhibition rate from approximately 20-30% in the BRT-COF+L group (estimated value, based on ferritin targeting and ferroptosis mechanism) to approximately 20-30% in the BRT-COF+L group. Figure 12The a curve jumped to 85.8%, an effect far exceeding what the dispersion improvement could explain, demonstrating the crucial role of active targeting in synergy with ferroptosis. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 The image shows the XRD characterization of BRT-COF. The horizontal axis, 2θ, represents the X-ray diffraction angle, and the vertical axis represents intensity.
[0022] Figure 2 This is the IR absorption spectrum of BRT-COF. The horizontal axis represents wavenumber, and the vertical axis represents transmittance.
[0023] Figure 3 This is the XPS full spectrum scan of BRT-COF. The horizontal axis represents binding energy, and the vertical axis represents intensity.
[0024] Figure 4 The images show TEM images and DLS analysis plots of BRT-COF. In the DLS plot, the horizontal axis represents hydrated particle size (Size), and the vertical axis represents the number distribution (Number).
[0025] Figure 5 The images show the UV-vis-NIR absorption and fluorescence emission spectra of BRT-COF. In the UV-vis-NIR absorption spectrum, the horizontal axis represents wavelength (Wavelength), and the vertical axis represents absorbance (Absorbance). In the fluorescence emission spectrum, the horizontal axis represents wavelength (Wavelength), and the vertical axis represents fluorescence intensity (FL Intensity).
[0026] Figure 6 This is a graph for evaluating in vitro photodynamic performance. The horizontal axis represents wavelength, and the vertical axis represents fluorescence intensity (FL Intensity).
[0027] Figure 7 This is a graph for evaluating in vitro photothermal performance.
[0028] Figure 8 For BRT-COF@HKN15 TEM images, DLS analysis, and Zeta potential maps were obtained. In the DLS map, the horizontal axis represents hydrated particle size (Size), and the vertical axis represents the number distribution (Number).
[0029] Figure 9 This is a graph for evaluating in vitro imaging performance.
[0030] Figure 10 These are fluorescent images of in vitro cell viability and death staining.
[0031] Figure 11 This is a flow cytometry graph showing the quantitative analysis of in vitro cell apoptosis. Apoptosis was detected using Annexin V-FITC / PI double staining. The horizontal axis represents the fluorescence signal of Annexin V-FITC (fluorescein isothiocyanate-labeled annexin V), and the vertical axis represents the fluorescence signal of PI (propidium iodide). The lower left quadrant (Q4), lower right quadrant (Q3), upper right quadrant (Q2), and upper left quadrant (Q1) represent surviving cells, early apoptotic cells, late apoptotic cells, and necrotic cells, respectively.
[0032] Figure 12 This is a diagram of an in vivo animal experiment.
[0033] Figure 13 This is a diagram from a safety experiment. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention.
[0035] Example 1: Preparation of BRT-COF Raw material weighing and reaction system setup: Weigh 0.06 mM of the substrate 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) BRT and 0.03 mM of the substrate tetra(4-pinacolylphenyl)methane TPPM and place them in a round-bottom flask (this ratio greatly reduces the generation of byproducts); then, add 10 mg of the catalyst tetra(triphenylphosphine)palladium; 4 mL of the reaction mixture toluene and 2 mL of ddH2O (the choice of organic solvent can determine the reaction yield and the crystallinity of 3D COF); 0.4 g of K2CO3; and finally add a magnetic stir bar.
[0036] Place the reaction system on a magnetic stirrer, connect a serpentine condenser, turn on the cooling water, and apply nitrogen protection. Set the temperature to 100 ℃, and adjust the speed of the magnetic stirrer to a point where the liquid surface sloshes slightly (this step directly determines the crystallinity of the product). React for three days.
[0037] Sample purification: Remove the magnetic stir bar, transfer the sample to a centrifuge tube, and let it stand for 5 minutes until the liquid surface separates to remove excess ddH2O. Add anhydrous ethanol to the final volume, vortex for 30 seconds, and then centrifuge. Centrifuge at 10000 r / min for 5-15 minutes at 20 °C, repeating three times. Discard the supernatant to remove substrate and a small amount of byproduct. Add ddH2O again to the final volume, vortex for 30 seconds, and then centrifuge. Centrifuge at 10000 r / min for 5-15 minutes at 20 °C, repeating twice. Discard the supernatant to remove alkali and palladium catalyst. Transfer the final precipitate to a clean centrifuge tube using ddH2O and freeze-dry. The final product is a green solid powder, BRT-COF.
[0038] Example 2: BRT-COF@HKN 15 Preparation Using ddH2O as a solvent, a BRT-COF dispersion with a concentration of 2 mg / mL (prepared in Example 1) and an HKN dispersion with a concentration of 1 mg / mL were prepared. 15 Ferrocyte homing peptide solution. Then, equal volumes of both were mixed thoroughly and sonicated at 4 °C for 10 min using an ultrasonic device with a power of 30 W. After sonication, the mixture was transferred to a shaker at 4 °C and continuously shaken at 250 r / min for 5 h. After shaking, the final product was transferred to an ultrafiltration tube with a molecular weight cutoff of 3 kDa for centrifugation purification to remove unbound free HKN from the system. 15Iron death homing peptide fragment. The supernatant from the ultrafiltration tube was finally collected to obtain BRT-COF@HKN with excellent water dispersibility. 15 Green nano-dispersion.
[0039] Test case 1. Characterization of the BRT-COF obtained in Example 1 like Figure 1 As shown, the prepared BRT-COF exhibits excellent crystallinity, with a sharp diffraction peak at 2θ = 4.25° in the XRD pattern, indicating a regular pore arrangement. It is noteworthy that the Suzuki cross-coupling reaction is an irreversible carbon-carbon bond formation reaction. Its thermodynamic irreversibility inherently conflicts with the "dynamic covalent chemistry" self-repair mechanism upon which COF crystallization depends. Therefore, existing technologies generally consider Suzuki coupling only suitable for constructing amorphous porous aromatic frameworks (PAFs). This invention overcomes this limitation. Its crystallinity originates from the pre-organized self-assembly of BRT and TPPM monomers at the toluene / water interface: the rigid planar conjugated structure (DAD configuration) of BRT is oriented in the hydrophobic phase, while the tetrahedral spatial configuration of TPPM extends from this hydrophobic layer into the aqueous phase, forming a thermodynamically favorable diamond-like carbon (dia) topological pre-organized conformation; the subsequent Suzuki coupling reaction kinetically captures and locks this metastable pre-organized conformation into a permanent 3D covalent framework. Therefore, this sharp diffraction peak not only represents high crystallinity, but also signifies the scientific feasibility of obtaining ordered 3D COFs through irreversible coupling reactions via a "pre-organization-locking" mechanism.
[0040] like Figure 2 As shown, in the infrared spectrum, brominated aromatic compounds are often found in the range of 600–500 cm⁻¹. -1 C-Br stretching vibrations occur nearby. For boronic acid ester structures, however, vibrations often occur around 1000 cm⁻¹. -1 Absorption related to the boron-oxygen framework is observed on both sides. The characteristic peaks are weakened in the final product. Furthermore, the product spectrum retains these aromatic framework signals, indicating that the final material is still dominated by an aromatic conjugated network, rather than monomeric decomposition products. This demonstrates the complete occurrence of the Suzuki coupling reaction at the chemical bonding level. These spectroscopic features indicate that a fully carbon-carbon bonded covalent framework has been effectively formed between BRT and TPPM, rather than a simple physical coating or partial coupling product. Compared to reversible covalent bonds such as imine bonds and boron ester bonds, this fully carbon-carbon bonded framework exhibits excellent chemical stability, avoiding the risk of hydrolysis of imine bond COFs in physiological environments (especially under the pH 5.5–6.5 conditions of the tumor microenvironment), thus laying the structural foundation for subsequent in vivo applications.
[0041] like Figure 3As shown, combined with XPS full-spectrum scanning, it can be observed that the S element on the BRT monomer was successfully introduced into the BRT-COF. Simultaneously, the disappearance of Br and B elements was also observed in the full-spectrum scan of BRT-COF. This elemental composition demonstrates that the pinacol ester group and the brominated group have completely participated in the Suzuki coupling reaction at the toluene / water interface, without significant substrate embedding or residue. This result is consistent with... Figure 2 The infrared spectral data corroborate each other and jointly support the mechanism of interfacial pre-organization-complete coupling: only in the pre-assembled state of the two-phase interface can the catalyst Pd(0) simultaneously and efficiently contact the brominated sites of BRT and the pinacol ester sites of TPPM, achieving near-complete conversion and ultimately forming a full carbon skeleton with a clear stoichiometric ratio and uniform structure.
[0042] like Figure 4 As shown in the TEM images, near-spherical primary nanoparticles form irregular secondary aggregates through stacking / aggregation. This morphology is highly consistent with the topology of a 3D interpenetrating network: the primary nanoparticles can be considered as individual domains of a dia topology, while their irregular secondary aggregates are macroscopic assemblies of multiple domains driven by hydrophobic-hydrophilic interfacial tension. DLS measurements revealed an average hydrated particle size of approximately 295 nm, reflecting the interfacial tension-driven aggregation of pure BRT-COF in a physiological aqueous phase due to the exposure of its hydrophobic framework. While this initial particle size is unfavorable for cellular uptake, it confirms the material's highly rigid 3D framework structure—if it were a flexible amorphous polymer, it would tend to form a loose, swollen state rather than dense aggregates in an aqueous phase.
[0043] 2. BRT-COF UV-vis-NIR absorption and fluorescence emission spectra like Figure 5As shown, BRT-COF exhibits broadband absorption characteristics in ddH2O and displays significant optical response in the visible to near-infrared region. In DMSO, its fluorescence emission peak is located at approximately 1024 nm, which is typical of the near-infrared II (NIR-II) window emission. This intrinsic emission is not dependent on exogenous dye loading, but rather originates from the synergistic effect of molecular framework engineering and a three-dimensional interpenetrating π-conjugated network: the benzo[1,2-c:4,5-c']bis([1,2,5]thiadiazole) unit in the BRT monomer is a strong electron acceptor (A), and the thiophene rings on both sides are electron donors (D), forming a DAD conjugated structure, whose HOMO-LUMO band gap is already in the near-infrared region; when the monomer is embedded into the 3D framework through Suzuki coupling, adjacent BRT units are connected through TPPM tetrahedral nodes to form a three-dimensional interpenetrating π-network. Unlike 2D COFs where interlayer π-π stacking easily leads to fluorescence quenching, the 3D interpenetrating structure of this invention effectively suppresses excessive interchain stacking through the steric hindrance effect of the 2-ethylhexyl group in the BRT side chain. Simultaneously, the three-dimensional rigid support of the tetrahedral nodes restricts intramolecular rotation / vibration (RIR mechanism), significantly reducing the nonradiative transition rate, thus allowing excited-state energy to be released primarily through fluorescence emission in the NIR-II region. For ease of comparison, both UV-vis-NIR absorption and fluorescence emission spectral data have been normalized.
[0044] 3. Performance evaluation of BRT-COF extracorporeal photodynamic therapy (PDT) BRT-COF dispersion (10 µg / mL) was prepared using ddH2O as solvent. DCFH-DA stock solution (10 mM) was prepared with methanol, then activated by alkaline hydrolysis with NaOH to generate the DCFH probe. The reaction was terminated with PBS and stored in the dark. Subsequently, the DCFH probe was mixed with the sample in a 96-well plate, and after irradiation with an 808 nm laser (100 mW / cm²) for 0, 1, 2, 3, 4, and 5 min, changes in ROS-related fluorescence signals were detected using a fluorescence microplate reader.
[0045] The results are as follows Figure 6As shown, BRT-COF exhibits significant ROS generation capability under 808 nm laser irradiation, with the signal gradually increasing with irradiation time. This photodynamic effect stems from the precise matching between the material's band structure and excited-state dynamics: the 808 nm photon energy is sufficient to excite the π-π* transition of the DAD unit in BRT-COF, forming an excited singlet state (S1); thanks to the restriction of intramolecular rotation by the 3D rigid framework, the efficiency of the S1 state reaching the excited triplet state (T1) via intersystem crossing (ISC) is significantly improved; the T1 state then transfers energy to the ground-state oxygen molecule (³O2), generating singlet oxygen (¹O2, Type II PDT mechanism). The rigid structure of the 3D interpenetrating network not only promotes the ISC process but also retains sufficient excited-state energy for ROS generation by suppressing nonradiative decay, thus achieving a balanced coexistence of photothermal conversion and ROS generation.
[0046] 4. Performance evaluation of BRT-COF extracorporeal photothermal therapy (PTT) Using ddH2O as the solvent, samples with a concentration of 50 / 100 µg / mL were prepared. 200 µL of each sample was added to an ELISA strip and irradiated with an 808 laser for 5 min (data was taken every 30 s). The laser power density was 0.5 / 1 W / cm². 2 ddH2O was used as the control group.
[0047] like Figure 7 As shown, BRT-COF exhibits good photothermal performance (temperature rises to 65 °C) and excellent photothermal stability (no significant decay after five cycles) under 808 nm laser irradiation, with a photothermal conversion efficiency (η) of approximately 32.1%. This photothermal effect and photodynamic effect are not in a competitive relationship, but rather originate from different relaxation channels of the same excited state energy level: part of the excited state energy is converted into lattice thermal vibration (PTT) through internal conversion (IC) and nonradiative relaxation, while another part is converted into the T1 state through ISC to drive ROS generation (PDT). Although the 3D rigid framework restricts intramolecular rotation primarily to enhance NIR-II emission, it still retains a moderate amount of nonradiative channels for photothermal conversion.
[0048] More importantly, the localized mild hyperthermia (below the tissue carbonization threshold) generated by PTT can dilate tumor blood vessels and increase blood perfusion, thereby improving the hypoxic microenvironment of the tumor. After the hypoxia is relieved, the concentration of ground-state oxygen molecules recovers, further enhancing the ROS production of PDT. At the same time, the ROS generated by PDT can destroy the tumor cell membrane structure, reduce the expression of heat shock proteins (HSPs), weaken the tumor's heat tolerance, and make subsequent photothermal killing more efficient. This positive feedback synergistic loop of "PTT improves oxygenation → PDT enhances → PDT destroys heat tolerance → PTT enhances efficacy" makes the anti-tumor efficacy of BRT-COF far exceed the simple sum of phototherapy alone.
[0049] Based on the above photothermal experimental data, the photothermal conversion efficiency of the BRT-COF was further calculated. As shown in formula (1): (1) in, The photothermal conversion efficiency of the sample; The highest temperature of the sample when it was continuously irradiated with an 808 nm laser to thermal equilibrium was recorded in real time by an infrared thermal imager. The initial ambient temperature is recorded in real time by an infrared thermal imager. This is a correction term for background heat loss caused by blank ddH2O and the sample cell under the same experimental conditions; The total power of the incident 808nm laser was measured by an optical power meter. The absorbance of the sample at 808 nm was measured by a UV-vis-NIR spectrophotometer.
[0050] Among them, the overall heat transfer coefficient The result was obtained by fitting the natural cooling curve of the sample after irradiation was stopped. According to... Define a dimensionless temperature-driven force, for With cooldown time A linear fit is performed, and the reciprocal of the slope is the heat conduction time constant. Then, the result is obtained by formula (2): (2) in, and The values represent the mass and specific heat capacity of each component in the system, respectively. Since the concentration of BRT-COF in this embodiment is low (100 µg / mL), its influence on heat capacity is negligible; therefore, the system's heat capacity is approximately contributed by ddH₂O. In this embodiment, the volume of ddH₂O quantitatively transferred is 200 µL, corresponding to approximately 0.2 g of water. The specific heat capacity of water is taken as 4.2 J·g⁻¹. -1 ·℃ -1The natural cooling curve of the blank ddH2O system under the same conditions can be used to obtain... Calculated based on this The calculation formula (3) is as follows: (3) in, This represents the highest temperature at which the blank ddH2O system reaches thermal equilibrium under the same conditions. After fitting, the sample system's... 95.173 (R) 2 =0.9909), blank ddH2O system It is 144.31 (R) 2 =0.9798). In this embodiment, the specific measured parameters are as follows: = 65℃, = 32.2 ℃, = 26.8 ℃, =1.320052, the total power of the incident 808 nm laser is 1 W. Substituting the above parameters into formula (1), the final calculated photothermal conversion efficiency of BRT-COF is approximately 32.1%.
[0051] The near-infrared II region BRT-COF material prepared by this invention has excellent photophysical properties.
[0052] 5. Regarding the BRT-COF@HKN obtained in Example 2... 15 Calculate the drug loading rate. HKN solutions with concentrations of 25, 50, 75, 100, and 200 µg / mL were prepared using ddH2O as the solvent. 15 Standard solution. Its absorbance at a specific wavelength was measured using UV-Vis, and the standard curve equation was established as follows: A =2.0063 C +0.0027, R 2 =0.9981. The absorbance A of the ultrafiltrate purified by centrifugation in Example 2 was measured at the corresponding wavelength as 0.02767. Substituting this value into the above standard curve equation, the content of free peptides in the ultrafiltrate was calculated, and thus the HKN was calculated. 15 The drug loading rate on BRT-COF was 27.7%.
[0053] 6 BRT-COF@HKN 15 Transmission electron microscopy images, particle size distribution and zeta potential like Figure 8 As shown, TEM results indicate that BRT-COF@HKN 15It exhibits a relatively uniform elliptical structure. DLS test results show that after processing with the peptide HKN... 15 After surface modification, the average hydrated particle size of the composite material in the aqueous system was significantly reduced from 295 nm in pure BRT-COF to 106 nm, and the polydispersity index (PDI) was optimized from 0.220 to 0.134. The significant decrease in hydrated particle size confirms that the introduction of the peptide-modified layer effectively suppressed the aggregation of hydrophobic COF particles in water, endowing the system with excellent dispersion and size uniformity.
[0054] Furthermore, zeta potential testing results showed that the surface potential before BRT-COF modification was -10.7 mV, which was improved by HKN. 15 After modification, BRT-COF@HKN 15 The Zeta potential significantly changed to +14 mV. This marked change in surface charge further confirms the presence of HKN. 15 The peptide has been successfully loaded onto BRT-COF.
[0055] This series of changes confirms that the HKN15 modification is not a simple physical adsorption, but rather follows an electrostatic self-assembly-hydration layer formation mechanism: the BRT-COF surface is negatively charged due to trace amounts of oxidized residual carboxyl / phenolic hydroxyl groups; HKN15 is rich in lysine (K) and histidine (H), carrying a strong positive charge at physiological pH, and densely adsorbs onto the COF surface through electrostatic interactions, forming a peptide corona. This corona, on the one hand, forms a dense hydration layer through hydrophilic amino acid residues (K, N, G), inhibiting the π-π aggregation of hydrophobic COF particles through steric hindrance and electrostatic repulsion; on the other hand, the surface charge is reversed to positive, endowing the material with affinity for the tumor cell membrane (negatively charged), laying the foundation for subsequent efficient endocytosis.
[0056] 7. BRT-COF@HKN 15 In vitro imaging performance evaluation In vitro fluorescence signal verification: A sample with a concentration of 100 µg / mL was prepared. 200 µL was added to each enzyme-labeled strip, with n=3 strips placed in parallel for each group. The fluorescence signal at excitation wavelengths of 808 / 980 / 1064 nm (laser power density of 100 mW / cm²) was detected using a near-infrared II fluorescence imaging device. 2 ).like Figure 9 As shown in Figure a, the fluorescence intensity reaches its maximum under detection conditions with a 1000 nm long-pass filter (LPF), and the emission signal can be tailed up to 1400 nm. The fluorescence intensity is expressed as the average gray value.
[0057] In vitro penetration depth assessment: Samples with a concentration of 100 µg / mL were prepared. Samples were loaded into capillaries with an inner diameter of 1.0 mm, arranged in parallel groups of n = 3. The samples were then subjected to laser power density of 100 mW / cm² under 1000 nm LPF conditions. 2 Excitation (excitation wavelength 808 nm). Capillaries were placed under chicken breast slices of 3, 5, 8, and 10 mm thickness to simulate tissue coverage conditions, and in vitro penetration performance was evaluated. Figure 9 As shown in b, this material still exhibits a recognizable fluorescence signal and good spatial resolution even when covering 10 mm of chicken breast. Here, distance (pixels) represents the distance in pixels.
[0058] This superior penetration performance stems firstly from the low tissue absorption and low scattering characteristics of the NIR-II window (1000–1700 nm); secondly, and more importantly, the signal is an intrinsic emission of the BRT-COF framework (such as...). Figure 5 The intrinsically emitted 3D covalent framework permanently locks the luminescent groups into the crystal lattice via C-C bonds, rather than using exogenous NIR-II dye loading. Exogenous dyes pose risks of leakage, photobleaching, and batch-to-batch variation, while the intrinsically emitted 3D covalent framework permanently locks the luminescent groups into the crystal lattice via C-C bonds, fundamentally eliminating signal attenuation and biosafety concerns caused by probe leakage. Therefore, Figure 9 The deep, high-resolution imaging observed in b provides direct evidence of the synergistic effect between material structural stability and photophysical properties.
[0059] 8: In vitro cell experiments Logarithmic growth phase mouse breast cancer 4T1 cells were seeded into six-well plates and cultured overnight to allow them to adhere (DMEM high-glucose basal medium + 10% fetal bovine serum + 1% penicillin antibiotics). Cells were randomly divided into 6 groups: (1) Control group; (2) BRT-COF group; (3) BRT-COF@HKN 15 Group; (4) Control+L group; (5) BRT-COF+L group; (6) BRT-COF@HKN 15 +L group. The corresponding materials (final concentration 80 µg / mL) were added according to the group, and after incubation for 12 h, the original culture medium was aspirated, and the cells were washed three times with PBS to remove any unabsorbed free material. Fresh DMEM complete culture medium was then added. For groups requiring light, an 808 nm laser was used to continuously irradiate for 5 min at a power density of 1 W / cm².
[0060] Calcein-AM / PI live / dead cell double staining analysis: After laser irradiation and incubation for 6 h, cells in each group were double-stained using a commercially available Calcein-AM / PI cell viability and cytotoxicity assay kit. Observation and photography were performed using a fluorescence inverted microscope (scale bar = 150 µm, e.g., ...). Figure 10 (As shown). Calcein-AM is calcein acetoxymethyl ester, and PI is propidium iodide. Results showed that the Control group, the light-only group (Control+L), and the drug-only group without light (pure BRT-COF group, BRT-COF@HKN) were different. 15 The cells in the group all exhibited strong, uniform green fluorescence (live cells), indicating that the nanomaterials described in this invention have excellent biocompatibility and almost no dark toxicity.
[0061] The significant technological advancement lies in the fact that, under illumination, the unmodified BRT-COF+L group exhibits limited cytotoxic effects due to its large crystal size and tendency to aggregate in the physiological environment, resulting in low cellular uptake efficiency (only a few red fluorescent spots are interspersed in the green fluorescent background under a microscope). In contrast, the BRT-COF@HKN group, which is the preferred technical solution of this invention... 15 The +L treatment group, due to the significant improvement in water dispersibility and colloidal stability caused by surface peptide modification, enabled the material to be efficiently internalized and taken up by tumor cells. Under the same illumination conditions, it released extremely strong photothermal / photodynamic synergistic killing efficacy, and the cells in the field of view were almost completely transformed into strong red fluorescence (dead cells). This intuitive result confirms that optimizing dispersibility through surface modification can significantly enhance the in vitro antitumor activity of the material.
[0062] Annexin V-FITC / PI Flow Cytometry Apoptosis Analysis: To further quantitatively assess the killing mechanism of nanomaterials on tumor cells, the commercially available Annexin V-FITC / PI apoptosis detection kit was used to quantitatively detect the apoptosis of cells treated in the above groups by flow cytometry (e.g., ...). Figure 11 (As shown). The flow cytometry scatter plot analysis results are in high agreement with the above-mentioned visual results of live and dead staining. Specifically, BRT-COF@HKN, which has been modified with peptide surface and exposed to light, 15 The total apoptosis rate (late apoptosis in Q2 + early apoptosis in Q3) of cells in the +L group reached 70.71%, significantly higher than the 18.87% in the unmodified BRT-COF +L group and other control groups. This unexpected technical effect (an improvement of approximately 274%) far exceeded the theoretical upper limit that could be explained by improved dispersion, demonstrating the key role of the ferritin-targeting-ferroptosis synergistic mechanism. Specifically, HKN 15After binding to ferritin on the surface of tumor cells, under 808 nm light irradiation, the ROS generated by BRT-COF directly attacks the ferritin shell, leading to Fe²⁺ oxidase. + / Fe³ + Ion release; free iron ions catalyze the generation of ·OH via the Fenton reaction, further triggering lipid peroxidation (LPO) and activating the ferroptosis pathway (GPX4 inactivation, MDA elevation). Therefore, the BRT-COF@HKN15+L group actually initiates three cell death programs simultaneously: direct thermal killing by PTT, ROS oxidative damage by PDT, and the lipid peroxidation chain reaction of ferroptosis. These three mechanisms superimpose each other, resulting in a significantly higher apoptosis / necrosis rate than the BRT-COF+L group, which relies solely on passive EPR targeting and lacks ferroptosis synergy.
[0063] 9: In vivo animal experiments Tumor model construction: Healthy female BALB / c purebred mice aged 4-6 weeks were selected, and 4T1 cells in the logarithmic growth phase were subcutaneously injected into the right lateral thigh of each mouse (the number of cells injected was approximately 1 × 10⁻⁶). 6 A subcutaneous xenograft tumor-bearing mouse model was established. The tumors were closely observed daily, and their long diameter (a) and wide diameter (b) were measured using calipers. When the average tumor volume reached approximately 100 mm³ (tumor volume is calculated using the formula: V = a × b), the tumor was considered complete. 2 / 2), tumor-bearing mice were randomly divided into 5 groups (n=4 per group): (1) Control group; (2) BRT-COF group; (3) BRT-COF@HKN 15 Group; (4) BRT-COF+L group; (5) BRT-COF@HKN 15 +L group.
[0064] In vivo administration and phototherapy: Mice in each treatment group were administered the corresponding material via tail vein injection (the dosage was uniformly calculated based on mouse body weight as 5 mg / kg). After administration and incubation for 24 h, the mice in the phototherapy group (groups 4 and 5) were fixed and continuously irradiated with an 808 nm laser (power density of 1.0 W / cm²) for 5 min. Throughout the treatment period, the relative tumor volume and weight of the mice were recorded every 2 days.
[0065] Sampling and Pathological Analysis: After 14 days of continuous monitoring and treatment, all mice were euthanized. Tumor tissues were completely dissected from each group of mice, photographed, and weighed. Subsequently, the tumor tissues were fixed in 4% polyoxymethylene solution, dehydrated, embedded in paraffin, sectioned, and stained with hematoxylin and eosin (H&E). The histopathological changes were observed under an optical microscope.
[0066] Results analysis: (1) Tumor volume, weight, and mouse body weight analysis: The dynamic growth curve of tumor volume in tumor-bearing mice during treatment is shown in the figure. Figure 12 As shown in Figure a, the final tumor weight statistics after treatment are as follows: Figure 12 As shown in b, the weight change curve during treatment is as follows: Figure 12 As shown in c.
[0067] The results showed that the Control group and the drug-only group without light exposure (BRT-COF group, BRT-COF@HKN) were effective. 15 The tumor volume of all groups showed a rapid and continuous malignant growth trend, with no significant difference between the groups, proving that the material itself has no significant inhibitory effect on tumor growth in vivo without near-infrared light excitation.
[0068] Of particular note, in the laser-treated group, the unmodified BRT-COF+L group showed only a partial tumor-suppressing effect because the material was prone to large-area aggregation in the physiological environment and was easily cleared by the reticuloendothelial system (RES) in the blood circulation after intravenous administration.
[0069] Conversely, BRT-COF@HKN is the preferred technical solution of this invention. 15 In group +L, the peptide surface modification endowed the material with excellent water dispersibility and colloidal stability, prolonging its in vivo circulation time. It also achieved high concentration accumulation in tumor tissue through a superior EPR effect, releasing a strong synergistic therapeutic effect under 808 nm laser irradiation. Tumor growth was devastatingly inhibited, and the final tumor weight was significantly lower than all other groups, with a tumor inhibition rate as high as 85.8% calculated based on tumor weight. Furthermore, the body weight change curves showed that the body weight of mice in each group did not decrease significantly during the experimental period, confirming the excellent in vivo biocompatibility and safety of the experimental material.
[0070] (2) H&E pathological section analysis of tumor tissue: H&E staining pathological images of tumor tissues in mice after treatment are shown below. Figure 12 As shown in d (scale bar = 50 µm). The pathological section results were completely consistent with the macroscopic volume / weight data. The tumor cells in the Control group and each individual control group had intact structures, large and deeply stained nuclei, were tightly packed, and were in a state of vigorous growth and division, with no obvious tissue damage. In contrast, in the BRT-COF+L group, only some cell degeneration was observed in local areas.
[0071] At BRT-COF@HKN 15 In the +L treatment group, extensive, contiguous tumor tissue necrosis and apoptosis were observed in the tissue sections. This manifested as complete disintegration of tumor cell structure, significant nucleus condensation, fragmentation, and dissolution, along with severe interstitial edema. This microscopic pathological evidence definitively confirms the efficacy of the BRT-COF@HKN method described in this invention at the cellular level. 15 The ability of nanomaterials to eliminate tumors through highly efficient phototherapy mediated in vivo.
[0072] like Figure 12 As shown, tumor growth was devastatingly inhibited in the BRT-COF@HKN15+L group, with a tumor inhibition rate as high as 85.8%, while the BRT-COF+L group only showed partial tumor inhibition. This difference was further amplified in the in vivo environment, and its mechanism follows a four-fold functional closed loop: The first layer – biocompatibility barrier and long circulation: HKN 15 The formed polypeptide canopy effectively shields the non-specific adsorption (opsonization) of the COF hydrophobic framework to plasma proteins, reduces the recognition by the reticuloendothelial system (RES), prolongs the in vivo circulating half-life, and provides a time window for the EPR effect; The second layer—synergistic effect of EPR and active targeting: Long circulation allows nanoparticles to leak into the tumor space through the high permeability of tumor blood vessels (EPR passive targeting), while HKN... 15 Active targeting is achieved through specific recognition of ferritin on the surface of tumor cells, and the synergy between the two results in a significantly higher drug enrichment concentration at the tumor site than in unmodified materials; The third layer—a triple cell death synergy: BRT-COF@HKN enriched at tumor sites. 15 Under 808 nm laser irradiation, PTT (local hyperthermia), PDT (ROS oxidation) and ferroptosis (lipid peroxidation) are initiated simultaneously. These three mechanisms cover different cell death pathways, avoiding drug resistance or marginal residues caused by a single mechanism. The fourth layer—positive feedback from the microenvironment: The gentle hyperthermia generated by PTT improves tumor hypoxia and enhances PDT efficiency; PDT disrupts cell membranes and heat shock proteins, reducing heat tolerance and thus boosting PTT; ROS disrupts ferritin, releasing Fe²⁺. + This triggers ferroptosis. This closed-loop mechanism originates from macroscopic tumor suppression (…). Figure 12 ab) to microscopic pathological damage ( Figure 12 d) All of them were verified to be consistent.
[0073] 10. BRT-COF hemolysis test A sample with a concentration of 200 µg / mL was prepared using PBS as a solvent, mixed with a fresh mouse red blood cell suspension, and the lysis effect of the sample on red blood cells was detected.
[0074] like Figure 13 As shown, the hemolysis rate of BRT-COF and BRT-COF@HKN15 at all concentrations was less than 2%, meeting the safety standards for biomaterials. For pure BRT-COF, its low hemolysis rate may stem from the limited contact between the hydrophobic framework and the erythrocyte membrane (rapid aggregation and precipitation reduce the interaction time). More importantly, after modification with HKN15, despite improved particle dispersibility and increased probability of contact with blood components, the hemolysis rate remained at an extremely low level, confirming the effectiveness of HKN15 in treating erythrocytes. 15 Biocompatibility barrier effect of peptide canopy: The densely adsorbed peptide layer forms a hydration barrier through hydrophilic amino acid residues, which physically blocks the direct contact between the hydrophobic surface of COF and the erythrocyte membrane. At the same time, although the positively charged surface (Zeta +14 mV) promotes tumor cell uptake, the electrostatic effect on the erythrocyte membrane (which is also negatively charged) is effectively buffered by the steric hindrance of the hydration layer, thus achieving a balance between targeting and blood compatibility.
[0075] Currently, cancer phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), precisely activates phototherapeutic agents (including photothermal / photosensitizers) at the tumor site using a light source of specific wavelengths, thereby achieving selective ablation of tumor tissue. It offers advantages such as being minimally invasive / non-invasive, having low side effects, being repeatable and controllable, and being able to be combined with real-time image guidance and synergistic effects. Nevertheless, the further application of single therapies in tumor ablation is limited due to certain limitations (e.g., PDT is susceptible to the hypoxic microenvironment of the tumor, while PTT may result in tumor margin residue due to uneven heat diffusion). To overcome these shortcomings and improve treatment efficacy, the combined application of PDT and PTT (such as PTT improving tumor oxygenation and enhancing the effect of PDT, and PDT / PTT jointly inducing immunogenic cell death) is widely recognized as an effective treatment strategy.
[0076] Real-time monitoring of the treatment site is crucial during treatment. Existing nanoprobes are mainly concentrated in the near-infrared I (NIR-I, 700-900 nm) "window," whose low tissue penetration depth severely hinders imaging performance. The near-infrared II (NIR-II, 1000-1700 nm) optical "window," due to its significantly reduced tissue absorption and scattering, offers new opportunities for high-resolution imaging guidance and efficient phototherapy of deep tissues. However, developing a multifunctional nanoplatform that combines efficient NIR-II absorption / emission, excellent photothermal / photodynamic properties, and good biocompatibility presents significant challenges. This invention overcomes this major challenge.
[0077] In summary, this invention constructs a three-dimensional interpenetrating covalent organic framework with all-carbon-carbon bonds through Suzuki cross-coupling of BRT and TPPM, overcoming the technical bias that irreversible coupling cannot achieve highly crystalline COFs; intrinsic NIR-II fluorescence emission of COF is achieved through framework engineering of DAD monomers and the RIR effect of the 3D interpenetrating network; a photothermal / photodynamic synergistic positive feedback loop is achieved through band-matching design; and finally, HKN... 15 Peptide modification achieves four functions: charge reversal, improved water dispersibility, ferritin targeting, and synergistic ferroptosis. The above principles and experimental data together demonstrate that the BRT-COF@HKN described in this invention... 15 Nanomaterials have significant technological advancements and clinical translational potential in the field of NIR-II imaging-guided synergistic tumor therapy.
[0078] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A method for preparing near-infrared II region three-dimensional covalent organic framework nanomaterials, characterized in that, Includes the following steps: Step (1): The reaction substrates 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) and tetra(4-pinazoylphenyl)methane were placed in a reaction vessel and subjected to a Suzuki cross-coupling reaction under alkaline conditions and catalyzed by a palladium catalyst. The solvent for the reaction was a mixture of toluene and ultrapure water, the reaction temperature was 80-120 °C, and the reaction was carried out under inert gas protection for 48-96 h. The molar ratio of the reaction substrates 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) to tetra(4-pinazoylphenyl)methane was 1-5:
1. Step (2): After the reaction is completed, let it stand to separate into layers, remove the aqueous phase, add anhydrous ethanol to the organic phase and mix well, centrifuge, discard the supernatant, wash the obtained precipitate alternately with anhydrous ethanol and ultrapure water, and freeze dry to obtain green solid powder, which is the near-infrared two-region three-dimensional covalent organic framework nanomaterial. It also includes step (3), which uses ferritin homing peptide to modify the surface of the near-infrared two-region three-dimensional covalent organic framework nanomaterial obtained in step (2); The ferritin homing peptide is HKN15 ferroptosis homing peptide. The surface modification process is as follows: the near-infrared two-region three-dimensional covalent organic framework nanomaterial dispersion is mixed with an equal volume of HKN15 peptide solution, ultrasonically treated at 3-5 ℃, followed by continuous oscillation, and then purified by ultrafiltration to remove free peptides. The supernatant is then collected.
2. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of the reaction substrate 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-C:4,5-C']bis([1,2,5]thiadiazole) to tetra(4-pina esterylphenyl)methane is 1.5-3.5:
1.
3. The preparation method according to claim 1, characterized in that, In step (1), the palladium catalyst is selected from one or more of tetra(triphenylphosphine)palladium, bis(dibenzylideneacetone)palladium, palladium acetate, and [1,1'-bis(diphenylphosphine)ferrocene]palladium dichloride; the alkaline conditions are provided by at least one of potassium carbonate, sodium carbonate, and cesium carbonate.
4. The preparation method according to claim 1, characterized in that, In step (2), the centrifugation speed is 10000-12000 r / min and the centrifugation time is 5-15 min; the alternating washing is to first wash with anhydrous ethanol 3 times and then wash with ultrapure water 2 times.
5. A near-infrared two-region three-dimensional covalent organic framework nanomaterial prepared by the method according to any one of claims 1 to 4.
6. The use of the near-infrared II three-dimensional covalent organic framework nanomaterial as described in claim 5 in the preparation of a near-infrared II fluorescence imaging-guided synergistic photothermal and photodynamic therapy drug for tumor treatment.
7. The use of the near-infrared II three-dimensional covalent organic framework nanomaterial as described in claim 5 in the preparation of near-infrared II imaging reagents.
Citation Information
Patent Citations
Organic compound capable of generating Raman spectrum signal and preparation thereof
CN115141213A
Covalent organic framework material with three-dimensional cage-type framework structure and preparation method of covalent organic framework material
CN118165230A